2021
DOI: 10.21037/atm-21-4049
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin improves myocardial injury via p38 MAPK/NF-KB p65 inhibition in lipopolysaccharide-induced mouse

Abstract: Background: Paeoniflorin (Pae) is an active compound with a variety of pharmacological effects. This aim was to investigate how Pae protects against myocardial injury and to explore its potential mechanism. Methods:We established a BALB/c mouse model that was intraperitoneal injection (i.p.) of RvE1 (25 µg/kg) or Pae (20 mg/kg) for 3 days, and then treated with lipopolysaccharide (LPS, 10 mg/kg, i.p.).The mice were randomly divided into the sham group, the LPS group, the LPS + RvE1 group, the LPS + Pae group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Numerous studies have demonstrated that the MAPK pathway is a classical pathway for apoptosis, with broad regulatory effects on various infectious diseases [48,[58][59][60]. Furthermore, the MAPK pathway has been widely confirmed to collaborate with NF-κB [61][62][63]. P65 is a crucial nuclear transcription factor [60,[64][65][66][67], and p38 has the ability to activate p65 and trigger apoptosis [60,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the MAPK pathway is a classical pathway for apoptosis, with broad regulatory effects on various infectious diseases [48,[58][59][60]. Furthermore, the MAPK pathway has been widely confirmed to collaborate with NF-κB [61][62][63]. P65 is a crucial nuclear transcription factor [60,[64][65][66][67], and p38 has the ability to activate p65 and trigger apoptosis [60,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…LPS, as endotoxin in Gram-negative bacteria, stimulates cardiac apoptosis and secretion of pro-inflammatory factors [ 13 ]. Therefore, LPS was widely used in the establishment of in vivo model of sepsis induced cardiomyopathy [ 14 ]. Results in this study also showed that LPS induced cardiac injury with up-regulation of biomarkers, including LDH, CK-MB and cTnI.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that p38 MAPK/NF-κB is involved in inflammation, and sustained activation of p38 MAPK/NF-κB was positively associated with cardiac injury [ 14 ]. LPS stimulated activation of p38 MAPK/NF-κB signaling, and inactivation of p38 MAPK/NF-κB signaling alleviated LPS-induced cardiac insufficiency [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LPS treatment results in a reduction of BAP31 levels in cardiomyocytes, while melatonin treatment restores BAP31 expression; BAP31 knockdown attenuates the beneficial effects of melatonin on mitochondrial function and ER homeostasis under LPS stress ( Zhang et al, 2020c ). Several studies have shown that p38 MAPK plays an essential role in SIMD, but the main focus of these studies is on its effect on the NF-κB inflammatory signaling pathway ( Wang et al, 2021d ; Rocca et al, 2021 ; Shyni et al, 2021 ), whether p38 MAPK plays a role in SIMD through the mechanism of Gp78 affecting the degradation of Mfn1 and Mfn2 deserves further investigation.…”
Section: The Role Of Mercs In Simdmentioning
confidence: 99%